Local and Systemic Concentrations of Pattern Recognition Receptors of the Lectin Pathway of Complement in a Cohort of Patients With Interstitial Lung Diseases - Vogt, Severin; Trendelenburg, Marten; Tamm, Michael; Stolz, Daiana; Hostettler, Katrin Esther; Osthoff, Michael (Frontiers in Immunology, 2020)
Background: The role of the lectin pathway of complement in the pathogenesis of interstitial lung diseases (ILDs) is largely unknown. Pattern recognition receptors (PRR) of the lectin pathway are involved in the clearance of apoptotic cells either via activation of the complement system or as direct opsonins. As recent findings suggest a role of apoptosis in the development of pulmonary fibrosis, the influence of plasma lectins has lately been considered in various ILDs, but data on local concentrations in the lungs are lacking. This study investigated the role of mannose-binding lectin (MBL), ficolin-2 and ficolin-3 in ILD patients. Methods: A case control study was conducted involving 80 patients with different forms of ILD as well as 40 control patients undergoing routine flexible bronchoscopy with broncho-alveolar lavage (BAL). Plasma and BAL fluid (BALF) levels of MBL, ficolin-2 and ficolin-3 were measured by enzyme-linked immunosorbent assays. Eight single-nucleotid polymorphisms (SNPs) of MBL and ficolin-2 were determined by genotyping and tested for their association with ILDs. Results: We included 35, 35, 10 and 40 patients with sarcoidosis, idiopathic pulmonary fibrosis (IPF), other ILD, and a control group, respectively. BALF but not plasma levels of the three PRR were significantly elevated in sarcoidosis patients compared to a control group without ILD (MBL: median 66.8 vs. 24.6 ng/ml, p = 0.02, ficolin-2: 140 vs. 58.8 ng/ml, p = 0.01, ficolin-3: 2523 vs. 1180 ng/ml, p = 0.02), whereas the frequency of the investigated SNPs was similar. In IPF patients, we observed numerically higher MBL plasma and BAL levels (plasma, median 1511 vs. 879 ng/ml, p = 0.44; BALF, 37.5 vs. 24.6 ng/ml, p = 0.7) as well as lower ficolin-2 plasma levels (plasma 1111 vs. 1647 ng/ml, p = 0.11). Conclusions: This is the first study to simultaneously assess systemic and local lectin pathway protein levels in ILD patients. Our data suggest an involvement of PRR of the lectin pathway in the pathogenesis of sarcoidosis given the significantly higher BALF levels. Additional analyses in a larger patient cohort are required to confirm a potential effect of local and/or systemic ficolin-2 levels in IPF patients.